Authentic Spoken English in YouTube Subtitles as a Source of EFL Learning Materials - Mieyrandha, Mieyrandha; Retsi, Olga Dona; Haryani, Tutik (ELT Worldwide: Journal of English Language Teaching, 2026)
Many students who are learning English as a Foreign Language (EFL) now use digital technology. YouTube is one of the easiest places to find real language input. There are videos with subtitles and natural spoken English. This study aims to analyze the linguistic features of authentic spoken English found in YouTube subtitles and explore their potential use in the creation of EFL learning resources. A qualitative descriptive methodology was utilized to examine selected YouTube videos with English subtitles, seeking to identify common traits of spoken discourse. The analysis revealed that the conversation exhibited numerous characteristics of natural discourse, including discourse markers, fillers, contractions, and informal language. These parts show how spoken English is natural and interactive, which is something that most textbooks don't have. The results show that YouTube subtitles can be helpful tools for students who want to learn how to speak English in real life.